Energy Efficient Time-Aware Traffic Grooming in Wavelength Routing Networks - Shuqiang Zhang; Dong Shen; Chun-Kit Chan (2010 IEEE Global Telecommunications Conference GLOBECOM 2010, 2010)
In this paper, we investigate both static and dynamic traffic grooming problems in a wavelength routing network, so as to minimize the total energy consumption of the core network, with the additional consideration of the holding times of the lightpaths and connection requests. In static case, all connection requests with their setup and tear-down times are known in advance, we formulate an Integer Linear Programming (ILP) to minimize the energy consumption. In dynamic case, we adopt a layered graph model called Grooming Graph and propose a new traffic grooming heuristics called Time-Aware Traffic Grooming (TATG) which takes the holding time of a new arrival connection request and the remaining holding time of existing lightpaths into consideration. We compare the energy efficiency of different traffic grooming policies under various traffic loads, and the results provide implications to choose the most energy-efficient traffic grooming policies under various scenarios.